Towards a legal definition of ecological restoration: Reviewing international, European and Member States' case law - Mendes, Ana (2022)
Ecological restoration is of crucial importance to mitigate the impact of human activity on the environment and preserve biodiversity and ecosystem services. Therefore, the concept of restoration is at the core of international and European Union (EU) environmental policy and governance. This article seeks to shed light on this concept in international and European case law. To this end, it reviews the definition, objectives and scope of restoration according to international scientific standards. It further distinguishes restoration from other related terms such as compensation, mitigation, conservation and rehabilitation. The article then analyses judgements rendered by the International Court of Justice, the Court of Justice of the EU and EU Member States' courts pertaining to restoration. It concludes that there are wide discrepancies in the use of the term restoration by the judiciary, in particular with regard to objectives, baselines and reference conditions. In light of these conclusions, the authors support the adoption of a legal definition of restoration.